2017
DOI: 10.1001/jamapediatrics.2016.2321
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Neighborhood Violence and Biological Stress in Children

Abstract: IMPORTANCE Exposure to violence continues to be a growing epidemic, particularly among children. An enhanced understanding of the biological effect of exposure to violence is critical.OBJECTIVE To examine the association between neighborhood violence and cellular and biological stress in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 39 publications
2
77
2
Order By: Relevance
“…Specifically, unemployment might more strongly affect individuals who spent their childhood in adverse neighborhoods. Childhood neighborhood disadvantage, for example, may increase stress reactivity (Hackman et al 2012), as shown in the association between varying neighborhood exposure during childhood and allostatic load and telomere length (Brody et al 2014; Theall et al 2017). Such compromised stress reactivity and cumulative “wear and tear” on physiological regulatory systems may influence how people perceive and cope with a stressor (Del Giudice et al 2011; Ellis and Boyce 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, unemployment might more strongly affect individuals who spent their childhood in adverse neighborhoods. Childhood neighborhood disadvantage, for example, may increase stress reactivity (Hackman et al 2012), as shown in the association between varying neighborhood exposure during childhood and allostatic load and telomere length (Brody et al 2014; Theall et al 2017). Such compromised stress reactivity and cumulative “wear and tear” on physiological regulatory systems may influence how people perceive and cope with a stressor (Del Giudice et al 2011; Ellis and Boyce 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Availability of healthy food outlets and residential walkability have been associated with glycemic control and overweight . In addition, a recent study reported that neighborhood violence is associated with increased levels of physiological and cellular stress markers, such as cortisol, in childhood …”
Section: Discussionmentioning
confidence: 99%
“…(20,21) In addition, a recent study reported that neighborhood violence is associated with increased levels of physiological and cellular stress markers, such as cortisol, in childhood. (22) Major strengths of this study include the prospective study design; the long-term follow-up of the participants, who were well characterized in both childhood and adulthood; and the objective highdensity measurement of neighborhood socioeconomic disadvantage in childhood. Our analysis fulfilled the assumptions in counterfactual mediation analyses and support causal inference.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to parental and household factors, an additional level of the environment to consider is the neighbour -hood. Disadvantaged neighbourhoods are linked to worse physical and mental health (Diez Roux & Mair, 2010), child verbal ability (Sampson, Sharkey, & Raudenbush, 2008), educational attainment (Boyle, Georgiades, Racine, & Mustard, 2007), cortisol functioning (Finegood, Rarick, Blair, & Investigators, 2017;Karb, Elliott, Dowd, & Morenoff, 2012;Theall, Shirtcliff, Dismukes, Wallace, & Drury, 2017), and adult cognitive functioning (Shih et al, 2011;Wight et al, 2006). Furthermore, given the relevance of assessing the experience of SES, it is important to consider families' perceptions of where they live.…”
Section: Neighbourhood Chaosmentioning
confidence: 99%